Erosion processes in Slovene Istria – part 2: Badlands - Zorn, Matija (Acta geographica Slovenica, 2009)
This article is a continuation of the article on soil erosion in submediterranean Slovene Istria from the first issue of the 2009 (49-1) journal. In this article we present geomorphic processes in the badlands of the same area (Dragonja River basin, SW Slovenia): sediment production from steep bare (Eocene) flysch slopes (rockwall retreat), movements of flysch debris along erosion gullies, and geomorphic processes on talus slopes. Sediment production of flysch rocks was determined by measurements on erosion plots and totals around 80 kg/m2 per year on average, which means that steep bare flysch rockwalls retreat at a speed of 35 to 50 mm per year. The badlands not only contain flysch walls but also slopes already eroded by erosion rills and gullies. A dam in one of the erosion gullies with the catchment area of 0.1 ha captured 20 tons of debris in fourteen months. Monitoring on talus slopes of the badlands revealed their dual character because erosion here alternates with accumulation.